Multicast tree construction: a nodes' relative leaving probability algorithm based on NICE in ALM. (2016) - Cui, Jianqun; Gao, Kuan; Ye, YongJia; Fan, Jing; Wu, Libing; Yang, Yi
Due to the existing defects of IP multicast, which is difficult to be expanded and managed, the researchers put forward application layer multicast. Real-time transmission is an important application field of application layer multicast technology. However, it has strict requirements for the network delay. This paper firstly analyses the delays composition of application layer multicast and the rule of the distribution of the nodes' session time. And then, according to these factors, we propose a multicast tree construction algorithm concerning the nodes' relative leaving probability based on NICE (NRLP-NICE). NRLP-NICE compares the distance among nodes and selects the centre nodes as the leaders to build new multicast tree. Meanwhile, NRLP-NICE switches the rule of the distribution of nodes' session time into nodes' relative leaving probability. NRLP-NICE is simulated by Omnet++. The simulated results show that NRLP-NICE has low control costs and average delay error percentage compared to NICE.